The Role of Ethnomathematics in Curricular Leadership in Mathematics Education - D'Ambrosio, Ubiratan (2021)
In this paper we share our reflections regarding the role of ethnomathematics in providing direction for leadership in mathematics education. Our arguments are grounded in an analy- sis of the world today, characterized by inequities and injustices, clamoring for a new social order. We contemplate the role of mathematics and mathematics education in improving the world for the benefit of future generations. In our vision, the Program Ethnomathematics is positioned as a theoretical framework capable of guiding practice and curriculum for a very different educational project, one that centers the children in a world of social equity and justice as well as a world in which humanity achieves equilibrium with and respect for nature and its resources. We end our reflections with some thoughts on the preparation of teachers and leaders for this alternate educational project.